Different outdoor professions have different risks – a cross‐sectional study comparing non‐melanoma skin cancer risk among farmers, gardeners and mountain guides. (27th May 2018) - Zink, A.; Tizek, L.; Schielein, M.; Böhner, A.; Biedermann, T.; Wildner, M.
Abstract: Background: One of the main risk factors for non‐melanoma skin cancer (NMSC), the most common cancer worldwide, is solar ultraviolet radiation (UVR). This has led to the recognition of NMSC as occupational disease for outdoor workers in several countries. However, outdoor professions are a very heterogeneous group with diverse daily activities and associated UVR exposure. Objective: To compare the prevalence of NMSC and associated risk behaviour in different outdoor professions. Methods: Cross‐sectional study among outdoor workers (farmers, gardeners, mountain guides) and indoor workers (office employees) as control group using a paper‐based questionnaire on UVR exposure and protective behaviour followed by a skin examination by a dermatologist. Results: A total of 563 participants (46.9% women, 46.9 ± 13.8 years) consisting of 348 outdoor workers (38.8% farmer, 35.3% gardener, 25.9% mountain guides) and 215 indoor workers were included in the study between March and September 2017. NMSC incl. actinic keratosis was diagnosed in 33.3% of mountain guides, 27.4% of farmers, 19.5% of gardeners and in 5.6% of indoor workers. Significant differences were seen between the outdoor professions with mountain guides at highest risk compared to farmers (OR = 2.6, 95% CI = 1.2–5.7). Substantial differences between the professions were also seen in skin cancer screening attendance rates (indoor worker 61.4%, mountain guides 57.8%, farmers 31.9%, gardeners 27.6%), daily UVR exposure during work and protective behaviour such as sunscreen use during work. Conclusion: Different outdoor professions have significant different risks for NMSC and show different risk behaviour. Tailoring prevention efforts to different professions based on their individual needs could be the key to lower the global burden of (occupational) NMSC.